Numerical investigation of liquid-solid erosion in unbonded flexible pipes. (October 2022) - Yu, Jianxing; Li, Haoda; Yu, Yang; Liu, Xin; Xu, Weipeng; Wang, Huakun; Liu, Pengfei
Abstract: Unbonded flexible pipes (UFPs) are widely used in marine engineering for oil transportation. This study aimed to assess the erosion of UFPs, and a simplified method to evaluate the erosion of the interlock carcasses of UFPs was proposed. Three widely used erosion models were used to predict erosion damage based on a user-defined FORTRAN subroutine, and the simulation results were compared. A series of computational fluid dynamics simulations was conducted. The effects of the geometric shape of the interlock carcass, fluid flow velocity, sand size, and sand concentration on the erosion rate were carefully studied. Based on the simulation results, a modified geometry factor for erosion prediction of the interlock carcasses of UFPs was proposed. Highlights: A simplified method was proposed to improve the accuracy of erosion prediction of Unbonded Flexible Pipes. User-defined UFD was incorporated into ANSYS CFX. Several important factors affecting the erosion of UFPs were studied. The erosion characteristic of large curvature UFPs and smooth pipes were compared.